Diagnosis and Treatment of a Neck Node Swelling Suspicious for a Malignancy: An Algorithmic Approach - Balm, A. J. M. (Hindawi Publishing Corporation, 2010)
Aim. To present an up-to-date algorithm incorporating recent advances regarding its diagnosis and treatment. Method. A Medline/Pubmed search was performed to identify relevant studies published in English from 1990 until 2008. Only clinical studies were identified and were used as basis for the diagnostic algorithm. Results. The eligible literature provided only observational evidence. The vast majority of neck nodes from occult primaries (>90%) represent SCC with a high incidence among middle aged man. Smoking and alcohol abuse are important risk factors. Asiatic and North African patients with neck node metastases are at risk of harbouring an occult nasopharyngeal carcinoma. The remainder are adenocarcinoma, undifferentiated carcinoma, melanoma, thyroid carcinoma and Merkel cell carcinoma. Fine needle aspiration cytology (FNAC) reaches sensitivity and specificity percentages of 81% and 100%, respectively and plays an important role as the second diagnostic step after routine ENT mirror and/or endoscopic examination. FDG-PET/CT has proven to be helpful in identifying occult primary carcinomas of the head and neck, especially when applied as a guiding tool prior to panendoscopy, and may induce treatment related clinical decisions in up to 60% of cases. Conclusion. Although reports on the diagnostic process offer mainly descriptive studies, current information seems sufficient to formulate a diagnostic algorithm to contribute to a more systematic diagnostic approach preventing unnecessary steps.